Wealth, Culture, and Corruption - Husted, Bryan W. (Journal of International Business Studies, 1999)
This paper examines the impact of national wealth, income distribution, government size, and four cultural variables on the perceived level of corruption in a country. The study finds that corruption is significantly correlated to GNP per capita, power distance, masculinity, and uncertainty avoidance. Significant interaction effects occur in collectivistic and high power-distance countries. Suggestions for future research are developed.